Cell adhesion molecule SC1/DMGRASP is expressed on growing axons of retina ganglion cells and is involved in mediating their extension on axons - Pollerberg, G. Elizabeth; Mack, Till G. A. (Developmental biology, 2002)
We determined expression and function of a cell membrane protein in the developing chick retinotectal system identified by a monoclonal antibody (mAb 4H5) and the corresponding antiserum. Our data revealed that the protein shares a series of properties, including the N-terminal amino acid sequence, with a cell adhesion molecule termed DM-GRASP, SC1, BEN, and JC7. It can therefore be considered identical with this molecule and is referred to as SC1/DMGRASP. In early development of the retinotectal system, SC1/DMGRASP is exclusively expressed on growing, far-projecting, tract-forming axons. Expression begins at the onset of retina ganglion cell axogenesis and its maximum overlaps with the phase of maximal axon extension. Later in development, SC1/DMGRASP appears on distinct laminae within plexiform layers in spatiotemporal correlation with synaptogenesis. In an in vitro assay system designed to study the elongation of RGC axonal processes on preexisting RGC axons, addition of SC1/DMGRASP antiserum specifically reduces lengths of axonal processes. In contrast, axonal growth on laminin or basal lamina preparations is not SC1/DMGRASP-dependent. Taken together, the data provide evidence for a role of SC1/DMGRASP in axonal elongation of SC1/DMGRASP-positive axons on such axons, thereby possibly contributing to the pathway and target finding mechanism of far-projecting, tract-forming central nervous system neurons.